Key technology and deployment strategy of 5G fronthaul transport networks - Fengchao FU; Peng WANG; Yu MAO; Yongmei HUANG; Yuanbao XIE; Aihua ZHANG; Guoqiang LIN (Dianxin kexue)
As one of the frontier communication technology,5G mobile communication technology has attracted much attention in China and abroad.Before large-scale deployment of 5G base station,the transport network must be planned and ready in advance.Four kinds of mainstream 5G fronthaul schemes were introduced and compared from the perspective of construction cost,technical maturity,construction difficulty and so on.Finally,considering 5G evolution in the existing network,some suggestions for the selection of 5G fronthaul schemes in different scenarios were given.